Penatalaksanaan Fisioterapi Pada Keterbatasan Lingkup Gerak Sendi Bahu Akibat Post Orif Fraktrus Haft Humerus Dextra (Management of Physiotherapy on Range of Motion Limitation due to Post Orif Fracture of Shaft Humerus Dextra) - Munzirin, Reni Mardika (Research of Service Administration Health and Sains Healthys, 2020)
Beground: Fractures of the humerus is an interruption of the continuity condition of the upper arm bone tissue  caused  by  collision  or  trauma  directly  or  indirectly.  Fractures  can  cause  pain,  swelling, spasms, decreased muscle strength and muscle wasting. Fractures of the humerus also resulted in limited  range  of  motion  (ROM)  joint  in  the  shoulder  and  elbow.  The  purpose  of  this  study  to determine whether there is an increase in the ROM on the right shoulder thathas limited the use of exercise therapy intervention  in the form of passive and active exercise and hold relax. Research using case study method in one type of cases with a single sample, is given a dose of 6 times the treatment  within  3  weeks.  The  result is  an  increase  in  ROM  right  shoulder  evaluated  using  a goniometer, the comparison between T1 to T6 is S. 40⁰ -0⁰ -120⁰ became S. 50⁰ -0⁰ -140⁰, F. 100⁰ -0⁰ -60⁰ into F. 110⁰ -0⁰ -70⁰ and R do not become R. 75⁰ -0⁰ -80⁰.